Taá¸¥lÄ«l TaqniyÄh Tarjamah Al-Qiá¹£ah Al-hÄriq fÄ« KitÄb QirÄ'atul Al-RÄsyidah: Wa Ta'tsiruhaa Fii Majaali Ta'limi Al-lughatil â€˜Arabiyah - Maulidiya, Amanda; Nursaadah, Siti; Supriadi, Rinaldi (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2024)
This article discusses the approach used in analyzing the translation techniques of the story of Al-Hariq. In this context, the study focuses on the translation strategies applied in the book Qiraatul Rashidah. The analysis is conducted to understand how the story of Al-Hariq is translated and presented in the context of the book. The study provides an in-depth insight into the process of translating the story and how it affects the reader's understanding and interpretation of the story. The technique of translating the story of Al-Hariq in the book Qiraatul Rashidah by using the theory of translation techniques proposed by Molina and Albir with a qualitative approach and descriptive analysis method. This research uses the library method to collect primary data in the source language text (BaSi) and target language text (BaSa) in the book Qiraatul Rasyidah. The conclusion and findings of this research are that there are five translation techniques found in the story of Al-Hariq out of 18 types of Molina and Albir's translation techniques, namely (1) transposition, (2) literal, (3) amplification, (4) shift, (4) description, and (5) reduction